IoT-Based LPG Gas Detection and Prevention withTemperature Monitoring - Love Mittal, Lovely Jadaun,Soni Singh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As we know Gas Leakage is a crucial problem in various fields like Industries, Firms, gas powered vehicles like CNG buses, cars etc. LPG Gas is highly flammable and can cause major damage to life and property. Gas cylinder explosion may be a serious disaster when it occurs in our kitchen. So here, we are making an IoT- based gas leakage detection system which reduces the chances of such accidents in kitchen. This system detects the gas leakage, alerts the concerned person by sending SMS and Email, closes the valve of the cylinder, regulates the buzzer, exhaust fan evacuates all the leaked gases. With the help of Temperature sensor, the cylinder’s temperature is continuously monitored. The former gas leakage system does not provide the facility of temperature monitoring.